Surgical intervention for pulmonary metastases - Pfannschmidt, Joachim; Egerer, Gerlinde; Bischof, Marc; Thomas, Michael; Dienemann, Hendrik (Deutsches Ärzteblatt, 2012)
Pulmonary metastases are often found in advanced metastatization from carcinoma of the colon and rectum, kidney, breast, prostate, and oropharynx. In addition, chorionic carcinoma, osteosarcoma, soft tissue sarcoma, testicular tumors, Ewing sarcoma,...
Gesehen am 14.11.2018